Cellulase stabilization by crosslinking with ethylene glycol dimethacrylate and evaluation of its activity including in a water–ionic liquid mixture. Issue 30 (8th March 2016) - Jamwal, Shivani; Chauhan, Ghanshyam S.; Ahn, Jou-Hyeon; Reddy, N. S.
Abstract : Synthesis of immobilized enzymes via crosslinking is an easy route to develop a biocatalyst with enhanced activity and recyclability. Abstract : Synthesis of immobilized enzymes via crosslinking is an easy route to develop biocatalyst with enhanced activity and recyclability. In the present study, cellulase from Aspergillus niger was crosslinked by ethylene glycol dimethacrylate (EGDMA) using ammonium persulphate (APS) as an initiator to obtain heat and pH stable crosslinked cellulase aggregates (CCAs) using 5% EGDMA and 1% APS for crosslinking. The pristine cellulase and the CCAs were characterized by various techniques. Their activity profiles were evaluated as a function of time, temperature and pH. The activity of the CCAs was further evaluated in 1-butyl-3-methyl imidazolium acetate [bmim][Ac] at the optimized conditions of time and temperature. Furthermore, the CCAs were reusable up to 12 repeat cycles with a retention of 58% of its initial activity after the 7th cycle in the hydrolysis of cellulose. An artificial neuron network (ANN) model was employed to correlate the relationship between process parameters and the %relative activity (RA). The predicted %RA values are in close agreement with the experimental values.